Jigsaw Learning: Peningkatan Hasil Belajar Matematika di MTs Negeri 1 Indramayu - Daryono Daryono (Jurnal Pendidikan Madrasah, 2021)
This research aims to improve the quality of the learning process and know the improvement of fractional material mathematical learning outcomes through the application of jigsaw-type cooperative learning models. This research uses action research methods carried out in stage 2 of the cycle. The research subject is Class IX-A MTs Negeri 1 Indramayu Year of Study 2017/2018. The results showed the learning process was natural and the quality of learning was more important than the results. In terms of the completion of student learning classically, namely in cycle I by 69%, it can increase to 100% in cycle II and in terms of the average value of evaluation results, namely in cycle I by 71.9 to 80 in cycle II with an increase of 8.1%. The results of this study also showed an increase in the level of student learning activity from 3.2 with the Category Of ModerateLy Active in cycle I to 4.6 active category in cycle II, with an increase of 1.4. The jigsaw type cooperative learning model can be applied to students in class IX madrasah Tsanawiyah.